Precision Agriculture for Efficient Water use Through Farmers’ Cooperatives in Iran - Golmohammadi, Farhood (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2025)
Agriculture is a highly water-consuming activity, and water resources worldwide are heavily exploited for food production. Pollution due to agricultural activities in Iran has increased during the last two decades. Pollutions are released into the atmosphere and thereafter pollute water and soil resources. Agriculture is heavily impacted by present climate change, and the potential reduction of harvest may lead to larger water requirements for sustainable yield and a decline of food security worldwide. This trend is increasing under population growth pressure, and recently increased agricultural land deals that led to transnational water abstraction to sustain food requirements. The concept of virtual water was introduced, that is, the water embodied in the production and trade of agricultural commodities, and assessment of virtual water trade between nations is now a means to quantify the worldwide budget of water resources. A key concept to virtual water quantification is the water footprint, developed for water use assessment in the production of goods, especially food. Water footprint and virtual water trade are used to assess the implications of worldwide trading strategies for food security, also pending climate warming. Nowadays agricultural methods developments that are productively, economically, environmentally, and socially sustainable are required immediately. The concept of precision agriculture is becoming an attractive idea for managing natural resources and realizing modern sustainable agricultural development. Plus pictures of the author’s field research visit from a modern and newly established greenhouse complex in Darmian County in south Khorasan province, south east of Iran. In this greenhouse complex utilizing modern technologies for desalination and suiting it for growing plants and fish farming etc. in this greenhouse complex planting trees of orange inside the greenhouse – as a byproduct and fancy and amusing tree – and jujube (Ziziphus jujube) and Grape (vinifera) trees and shrubs – as a windbreaker and sunshade trees – outside the greenhouse, plus utilizing and selling their products. This greenhouse complex was established by loans and the help of the central government, agricultural bank, and local people in this deprived and remote area with a high degree of salt in its water and soil. In this article, the author discusses and states the most important aspects of precision agriculture for ecological and environmental benefits through farmers’ cooperatives for organizing collective action.